2012
DOI: 10.1111/j.1939-1676.2012.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I in Racing Standardbreds

Abstract: Background Upper reference limits for cTnI have not been established for healthy Standardbred racehorses. Objectives To establish cTnI upper reference limits for Standardbred racehorses and determine if increases in plasma cTnI concentration can be detected in 1–2 hours after a race. Animals Samples were obtained from 586 apparently healthy Standardbreds aged 2–14 years before racing and from the winners of 144 races 1–2 hours after the end of the race. Methods Prospective, observational study; convenience sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Seven research studies in horses have evaluated cTn concentrations in normal horses after nonendurance exercise. None of these studies identified significant increases in cTn concentrations partly as a consequence of the study population sizes (15, 28, 6, 24, 26, and 15 horses, respectively) but also as a result of the use of older generation, conventional sensitivity assays that have a higher LoD . We identified significant increases in cTn, using the hscTnT assay, in horses after high‐intensity, short‐duration racing exercise.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Seven research studies in horses have evaluated cTn concentrations in normal horses after nonendurance exercise. None of these studies identified significant increases in cTn concentrations partly as a consequence of the study population sizes (15, 28, 6, 24, 26, and 15 horses, respectively) but also as a result of the use of older generation, conventional sensitivity assays that have a higher LoD . We identified significant increases in cTn, using the hscTnT assay, in horses after high‐intensity, short‐duration racing exercise.…”
Section: Discussionmentioning
confidence: 73%
“…application of established reference population, URL). In horses, a weak positive age, but not sex, correlation has been corroborated in 1 study of 586 Standardbreds at rest . Age correlations also have been explored in subjects undergoing exercise challenges, and in a recent cTnT postexercise study of humans using a high‐sensitivity assay, no age correlation was found between age and peak postexercise cTn concentrations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…51 Troponin levels and their behavior in association with anesthesia, racing, training, and endurance exercise has also been studied. [52][53][54][55][56] Increased CTNI levels in horses with colic support a less favorable prognosis and are associated with increased ventricular arrhythmias postoperatively. In one study, the combination of high CTNI levels postoperatively and high lactate levels preoperatively were significantly associated with nonsurvival.…”
Section: Biochemical Changesmentioning
confidence: 99%